Foreign Body Granuloma Induced by Submucosal Lifting Agent Mimicking Adenoma or Colorectal Carcinoma - Ali, MD, Mahmoud; Maloney-Patel, MD, Nell; Zhou, MD, PhD*, Zhongren (North American Journal of Medicine and Science, 2021)
Foreign bodies used during surgeries and endoscopy procedures may elicit inflammatory reactions and granuloma formation. The resultant lesion may mimic polyps or tumors, which require cautious interpretation. Here we reported that 69-year-old patient with history of treated rectal cancer underwent surveillance colonoscopy where a tubular adenoma was found in the cecum. A follow-up endoscopy found a flat polyp at the ileocecal valve. Right hemicolectomy was performed. On examining the specimen, two lesions were identified in the wall of the ileocecal valve area. Microscopically, there were foreign body giant cell granulomas filled with eosinophilic amorphous material which is consistent with an inflammatory reaction caused by submucosal lifting material injection used during colonoscopy for polypectomy. The granulomas mimicked recurrence of colorectal carcinoma. Therefore, surgeons and pathologists should be aware of the inflammatory reaction elicited by the new lifting agents that may resemble polyps or tumors. [N A J Med Sci. 2021;1(1):001-003. DOI: 10.7156/najms.2021.1401001]